Breaking boundaries: role of the brain barriers in metastatic process - Nasim Izadi; Peter Solár; Klaudia Hašanová; Alemeh Zamani; Maryam Shahidian Akbar; Klára Mrázová; Martin Bartošík; Tomáš Kazda; Roman Hrstka; Marek Joukal (Fluids and Barriers of the CNS)
Abstract Brain metastases (BMs) are the most common intracranial tumors in adults and occur 3–10 times more frequently than primary brain tumors. Despite intensive multimodal therapies, including resection, radiotherapy, and chemotherapy, BMs are associated with poor prognosis and remain challenging to treat. BMs predominantly originate from primary lung (20–56%), breast (5–20%), and melanoma (7–16%) tumors, although they can arise from other cancer types less frequently. The metastatic cascade is a multistep process involving local invasion, intravasation into the bloodstream or lymphatic system, extravasation into normal tissue, and colonization of the distal site. After reaching the brain, circulating tumor cells (CTCs) breach the blood–brain barrier (BBB). The selective permeability of the BBB poses a significant challenge for therapeutic compounds, limiting the treatment efficacy of BMs. Understanding the mechanisms of tumor cell interactions with the BBB is crucial for the development of effective treatments. This review provides an in-depth analysis of the brain barriers, including the BBB, blood-spinal cord barrier, blood-meningeal barrier, blood-arachnoid barrier, and blood-cerebrospinal fluid barrier. It explores the molecular and cellular components of these barriers and their roles in brain metastasis, highlighting the importance of this knowledge for identifying druggable targets to prevent or limit BM formation.